Sustainable and water engineering : theory and practice - Chandrappa, Ramesha (Wiley, 2014)
Ensuring safe and plentiful supplies of potable water (both now and for future generations) and developing sustainable treatment processes for wastewater are among the world's greatest engineering challenges. However, sustainability requires investment of money, time and knowledge. Some parts of the world are already working towards this goal but many nations have neither the political will nor the resources to tackle even basic provision and sanitation. Combining theory and practice from the developing and developed worlds with high- and low-tech, high- and low-cost solutions, this book discusses fundamental and advanced aspects of water engineering and includes: Water resource issues including climate change, water scarcity, economic and financial aspects requirements for sustainable water systems. Fundamentals of treatment and process design. Industrial water use and wastewater treatment. Sustainable effluent disposal. Sustainable construction principles With integrated theory, design and operation specifications for each treatment process, this book addresses the extent to which various treatment methods work in theory as well as how cost effective they are in practice. It provides a nontechnical guide on how to recover and reuse water from effluent, which is suitable for those in water resource management, environmental planning, civil and chemical engineering.